Do children undergoing bilateral myringotomy with placement of ventilating tubes benefit from pre-operative analgesia? A double-blinded, randomised, placebo-controlled trial. Issue 8 (12th July 2018) - McHale, B; Badenhorst, C D; Low, C; Blundell, D
Abstract: Objective: A double-blinded, randomised, placebo-controlled trial was conducted to determine whether routine pre-operative analgesia is beneficial in reducing post-operative ear pain following bilateral myringotomy and tube placement. Methods: Forty-five children (aged 3–15 years) were randomised to receive either pre-operative analgesics (paracetamol and ibuprofen) ( n = 21) or placebo ( n = 24). All children underwent sevoflurane gas induction with intranasal fentanyl (2 mcg/kg) to reduce the incidence of emergence agitation. Post-operative pain scores were measured using the Wong-Baker Faces Pain Rating Scale. Median pain scores taken 90 minutes post-surgery, and the highest pain score recorded prior to 90 minutes, were analysed. Results: There were no statistical differences between the median pain scores at 90 minutes or subsequent need for rescue analgesia. Emergence agitation did not occur in any child. Inadvertent ear trauma, use of an intravenous cannula or airway adjunct did not affect pain scores. Conclusion: Routine pre-operative analgesia does not reduce pain scores in the early post-operative period. Simple analgesics are effective for rescue analgesia in the minority of cases.